2020
DOI: 10.3389/fmicb.2020.01680
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-Mediated Synthesis of Porous Titanium Dioxide Nanoparticles From Withania somnifera Root Extract: Broad-Spectrum Attenuation of Biofilm and Cytotoxic Properties Against HepG2 Cell Lines

Abstract: There is grave necessity to counter the menace of drug-resistant biofilms of pathogens using nanomaterials. Moreover, we need to produce nanoparticles (NPs) using inexpensive clean biological approaches that demonstrate broad-spectrum inhibition of microbial biofilms and cytotoxicity against HepG2 cell lines. In the current research work, titanium dioxide (TiO 2 ) NPs were fabricated through an environmentally friendly green process using the root extract of Withania somnifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Biogenesis has grown rapidly in modern nanotechnology over the last few decades. The eco-friendly synthesis of nanoparticles has seen tremendous progress in nanoscience and its application in a wide range of fields such as the catalysis, antimicrobial [3], anticancer [4], target-specific drug delivery [5], and agriculture [6] fields. Recently, several biosynthesis methods have been suggested in order to develop potential sustainable synthesis techniques to reduce the use of hazardous materials for nanomaterials [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogenesis has grown rapidly in modern nanotechnology over the last few decades. The eco-friendly synthesis of nanoparticles has seen tremendous progress in nanoscience and its application in a wide range of fields such as the catalysis, antimicrobial [3], anticancer [4], target-specific drug delivery [5], and agriculture [6] fields. Recently, several biosynthesis methods have been suggested in order to develop potential sustainable synthesis techniques to reduce the use of hazardous materials for nanomaterials [7].…”
Section: Introductionmentioning
confidence: 99%
“…The green route is the more suitable option for nanoparticle synthesis, since it is more sustainable and ecofriendlier, while physical and chemical methods for synthesis are also possible [18]. Several researchers successfully synthesized TiO2 using eco-friendly plant materials such as leaves [3], roots [4], and fruits [19] for dye degradation. A range of phytochemicals and bioactive compounds have been found in common aqueous extracts from various medicinal plants that work as non-toxic capping and reducing agents, and shape and size control agents for synthesized nanoparticles [7,20].…”
Section: Introductionmentioning
confidence: 99%
“…The result in agreement with the previous nding where a confocal microscopic analysis revealed that titanium oxide nanoparticles synthesized using Withania somnifera root extract inhibited the biolms formation of E. coli, P. aeruginosa, L. monocytogenes, S. marcescens, and methicillin-resistant S. aureus (MRSA) on the glass surface. 46 Further analysis of the alterations on the biolm's architecture by the treatment of TiO 2 -NPs was studied using scanning electron microscopy. The electron micrographs of control and TiO 2 -NPs treated biolms of test bacteria are shown in Fig.…”
Section: Microscopic Analysis Of Biolms Inhibition On Glass Surface Usingmentioning
confidence: 99%
“…Titanium oxide nanoparticles have a broad spectrum of applications like antibacterial, cosmetics, photocatalyst, wastewater treatment, and other medical fields. In fact, they are among the most extensively utilized nanoparticles attributed to their superior properties like non-toxic, stable, safe, and having surface activity (Al-Shabib et al, 2020). For instance, a study done by Narayanan et al showed that TiO 2 NPs prevented the growth of bacterial pathogens via the generation of ROS, DNA, and cell membrane damage (Narayanan et al, 2021).…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 99%
“…Their results showed that at a concentration below MIC (0.5×MIC), TiO 2 NPs exhibited a significant inhibitory effect on biofilm development (43-71%) and mature biofilms (24-64%) in pathogens like P. aeruginosa, E. coli, Listeria monocytogenes, MRSA, Serratia marcescens, and Candida albicans. Consequently, they inferred that excessive ROS generation followed by cell death could be the possible cause for the compromised biofilm development in TiO 2 NP-treated pathogens (Al-Shabib et al, 2020).…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 99%